Multi-objective optimization model for sustainable Indonesian electricity system: Analysis of economic, environment, and adequacy of energy sources. (September 2015) - Purwanto, Widodo Wahyu; Pratama, Yoga Wienda; Nugroho, Yulianto Sulistyo; Warjito,; Hertono, Gatot Fatwanto; Hartono, Djoni; Deendarlianto,; Tezuka, Tetsuo
Abstract: This paper presents a multi-objective optimization model for a long-term generation mix in Indonesia. The objective of this work is to assess the economic, environment, and adequacy of local energy sources. The model includes two competing objective functions to seek the lowest cost of generation and the lowest CO2 emissions while considering technology diffusion. The scenarios include the use of fossil reserves with or without the constraints of the reserve to production ratio and exports. The results indicate that Indonesia should develop all renewable energy and requires imported coal and natural gas. If all fossil resources were upgraded to reserves, electricity demand in 2050 could be met by domestic energy sources. The maximum share of renewable energy that can be achieved in 2050 is 33% with and 80% without technology diffusion. The least cost optimization produces lower generation costs than the least CO2 emissions, as well as the combined scenario. Total CO2 emissions in 2050 are five to six times as large as current emissions. The least CO2 emissions scenario can reduce almost half of the CO2 emissions of the least cost scenario by 2050. The proposed multi-objective optimization model leads some optimal solutions for a more sustainable electricity system. Highlights: An optimization model developed to rise the role of renewable energy electricity. The model can assess an adequacy of local energy sources. Optimizing cost of generation or CO2 emissions alone leads suboptimal solutions. Multi-objective optimization can identify optimal solution for generation mix.